Newborn Screening for Thalassemia and Hemoglobinopathies in a Community Hospital - Jarucharoenporn, Somchai (Journal of The Department of Medical Services, 2021)
Background : Newborn screening hemoglobin typing (NBS Hb typing) using spot blood was early diagnosed for thalassemias and hemoglobinopathies in neonates at 48 hours of age.Objectives : To identify the incidence of thalassemias, other hemoglobinopathies and to assess the association between thalassemias and neonatal hyperbilirubinemia.Methods : A retrospective descriptive study was done by reviewing the data of neonates born in a community hospital from 15th February 2017 to 28th February 2018. Those who were in critical conditions and were transferred to another hospital were excluded. Spot blood from heel prick of all neonates was collected at 48 hours after birth and sent for Hb typing test using isoelectric focusing method (IEF) and microbilirubin test.Results : A total of 755 neonates were enrolled during the study period (91.3% of total live births). The incidence of thalassemia and hemoglobinopathies was 36.69% (n=277). The three highest incidences were Hb E trait 20.66% (n=156), alpha thalassemia-1 trait 8.74% (n=66) and, Hb E trait with alpha thalassemia-2 3.17% (n=24) respectively. The incidence of neonatal hyperbilirubinemia was 20.66% (n=156). There was no statistically significant association between thalassemia and neonatal hyperbilirubinemia.Conclusions : The incidence of thalassemia and hemoglobinopathies in neonates using IEF was similar to the incidence reported using the standard method. This technique can be practically done in a community hospital. However, there was no statistically significant association between thalassemia and neonatal hyperbilirubinemia.